A Qualitative Analysis on Integrated Approach Towards Teachers' Burnout and Work Engagement in Indian HEIs - Rajak, Rupesh; Chandra, Bibhas (Prabandhan: Indian Journal of Management, 2017)
This article attempted to extend the understanding of burnout and work engagement in teachers in higher educational institutions and to find out probable factors in the Indian context. Data were collected from 60 university teachers through unstructured questionnaires. Out of those 60 teachers, 33 were selected for follow up interviews. Inductive content analysis was used for data analysis using a CAQDAS package named ATLAS.ti 7. Five new factors from the Indian context emerged out from this study, that is, interaction with students, teaching methods, flexible timingÂ and long break, unnecessary rules and regulations, and better HR policies. These factors could be the input towards future studies in academic development as well as for employee well-being and productivity.